CSF biological antioxidant potentials may differentiate neurodegenerative diseases—A preliminary report. Issue 2 (13th December 2017) - Kawai, Takayuki; Sakakibara, Ryuji; Bujo, Hideaki
Abstract: Oxidative stress has a significant impact on neurodegenerative diseases. Biological antioxidant potential (BAP) is a rapid measure of total antioxidant properties in the serum. However, few studies measured BAP in cerebrospinal fluid (CSF). We measured CSF BAP in patients with neurodegenerative disease. We had 17 patients with Alzheimer's disease (AD), nine with dementia with Lewy bodies (DLB), 10 with Parkinson's disease (PD), 11 with multiple system atrophy (MSA) patients, with the same background, and 19 healthy subjects as normal controls. We measured CSF BAP using a Free Radical Elective Evaluator. As a result, CSF BAP level in patients with neurodegenerative disease was higher than that in controls. In particular, CSF BAP level in patients with AD was higher than that in patients with DLB ( P < 0.05). We also found a close relationship between CSF Tau pT181/beta‐amyloid ratio and BAP in patients with AD ( P < 0.01), although this relationship was not found in patients with DLB. In conclusion, CSF BAP may help differentiating AD and DLB.